Development and Validation of a Two-Tier Multiple Choice Instrument to Assess Students’ Science Process Skills in Acid-Base Chemistry - Andaria, Meri; Hadiwinarto, Hadiwinarto (Yayasan Darussalam Bengkulu, 2023)
This study aims to develop and validate a two-tier multiple choice (TTMCQ) instrument to measure senior high school students’ science process skills (SPS) in acid-base chemistry. Following Borg and Gall’s modified research and development design (nine stages), the instrument was developed, validated, and tested in two public high schools in Bengkulu, Indonesia. Validation involved content experts, assessment specialists, and experienced chemistry teachers. Field trials were conducted with 119 students, and data were analyzed for validity, reliability, item difficulty, and discrimination indices. Results show that the TTMCQ instrument demonstrated strong validity, high reliability, appropriate difficulty distribution (53% easy, 42% medium, 5% difficult), and sufficient discriminating power. Teachers reported positive perceptions, noting that the instrument effectively challenges students’ reasoning and enhances their SPS. The study highlights the potential of TTMCQ instruments as practical tools for formative and summative assessment in science education.